Comparison of Doppler ultrasonic and oscillometric devices (with or without proprietary optimisations) for non-invasive blood pressure measurement in conscious cats - Cerna, Petra; Archontakis, Panos E; Cheuk, Hester Ok; Gunn-Moore, Danièlle A (Journal of feline medicine and surgery, 2021)
OBJECTIVES: This study compared Doppler and oscillometric (PetMAP+) devices (with or without proprietary optimisations) for the non-invasive measurement of blood pressure in conscious cats. METHODS: Twenty-three cats were enrolled; however, five were excluded as fewer than five measurements were obtained for each assessment. All measurements were obtained according to American College of Veterinary Internal Medicine consensus guidelines. Oscillometric device modes A and B were operated according to the manufacturer's guidelines. Doppler and oscillometric devices were used alternately as the first device. RESULTS: Systolic arterial blood pressure (SAP) measurements were obtained by Doppler (SAPd) and oscillometry; the mean of each set of five values was used for statistical analysis. There was a significant difference between SAPd and SAP measurements in oscillometric modes A (P <0.001) and B (P <0.001). While both modes measured SAP higher than SAPd, B had a smaller bias (+15.72 mmHg) and narrower limits of agreement (LOA). There was also a significant difference between SAPd and mean arterial pressure (MAP) on oscillometric modes A (P = 0.002) and B (P <0.001). Both modes' MAP readings were lower than SAPd and oscillometric A MAP was closer to SAPd (-14.94 mmHg), with a smaller bias and narrower LOA. CONCLUSIONS AND RELEVANCE: The findings support that Doppler and oscillometric devices cannot be used interchangeably, with or without proprietary optimisations. Methodology should always be taken into account and reference intervals (RIs) need to be defined for the different methodologies. Until methodology-specific RIs are published, definitive diagnosis of hypertension and sub-staging of patients with kidney disease according to the International Renal Interest Society guidelines remains challenging.
Keywords: Cats; Ultrasonography, Doppler; Animals; Ultrasonics; měření krevního tlaku; krevní tlak; oscilometrie; Blood Pressure Monitors; ultrazvuk; Blood Pressure; monitory krevního tlaku; Blood Pressure Determination; Oscillometry; ultrasonografie dopplerovská; kočky; zvířata